2018
DOI: 10.1007/s00381-018-3825-7
|View full text |Cite
|
Sign up to set email alerts
|

Subdural empyema due to Salmonella paratyphi B in an infant: a case report and review of literature

Abstract: Intracranial infection due to Salmonella is uncommon in children. Subdural empyema (SDE) is described with Salmonella typhi as a complication of meningitis. We report a 6-month-old infant with SDE secondary to Salmonella paratyphi B who had presented with prolonged fever and enlarging head. A literature review of Salmonella SDE in infants with respect to clinical course and outcome is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…To our knowledge, this is the first study to characterize subdural empyema in neonates after acute bacterial meningitis, although some case series can be found in the literature [15,18,19]. This study shows that subdural empyema complicates 18% of all neonates with bacterial meningitis.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…To our knowledge, this is the first study to characterize subdural empyema in neonates after acute bacterial meningitis, although some case series can be found in the literature [15,18,19]. This study shows that subdural empyema complicates 18% of all neonates with bacterial meningitis.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies found Streptococcus agalactiae, Listeria monocytogenes and Enterobacteriaceae to be important pathogens of subdural empyema in neonates with bacterial meningitis [29,31,32], although some important pathogens, including Haemophilus influenza type b, S. aureus, Salmonella spp. and Neisseria meningitis have been reported in the literature [15,18,19,33]. The incidence of neonatal GBS sepsis has declined in the past decade, mostly due to current infection control and preventive strategies that have worked successfully to reduce maternal colonization and vertical transmission [7,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations